Chair in Pediatric Surgery - Graña, Francisco (1922)
Inaugural lecture of the course of 1922, Department of Paediatric Surgery, by Dr. Francisco Grana, Professor of Pediatric Surgery and Orthopedics at the Faculty of Medicine of Lima, the National Academy of Medicine, of the Peruvian Society of Surgery.